Methodology for creating new scenes through the use of thematic relations for innovative designs. Issue 1 (3rd April 2017) - Georgiev, Georgi V.; Sumitani, Naofumi; Taura, Toshiharu
Abstract: In order to support the design of products with innovative desired functions (creating the desired functions), this study aims to develop a methodology to create new scenes in which a new product may be used by synthesizing the existing scenes. The development of this methodology focused on thematic relations, which are the relationships between two objects through a thematic scene, such as "an apple is cut by knife." Thematic relations enable us to represent and manipulate the scenes in a computational manner. In particular, we highlighted the synthesis of the scenes which belong to the different contexts (periods in time, culture, and technology). We propose a specific methodology in which thematic relations are used to construct a database of existing scenes and then create a new scene using this database. This methodology was implemented in a computer system. Case studies were provided to demonstrate the use of this system.